Zero-energy construction technology as a barrier for strengthening the position on the market on the basis of a nearly zero-energy facility. (2017) - Jerzak, Karolina
Abstract: The main aim of the following thesis is to present an analysis of the effectiveness of using alternative energy sources, when it comes to the all year round functioning of the facility on a chosen example. The starting point for a further analysis is the theoretical approach to sustainable construction in the context of the creation and strengthening barriers when it comes to reinforcing the position of a medium sized construction company on the Polish market. When forming sources of competitive advantage enterprises very often involve themselves in innovative activities such as new technologies having to fulfil the requirements set both by the investors and most importantly through changing legal conditions being put in place to protect energy resources. The following article will present the results of an analysis conducted on an nearly zero-energy facility possessing the LEED PLATINUM certificate executed by a medium sized construction company functioning on the Polish market as a general executor.